2016
DOI: 10.1038/mp.2016.125
|View full text |Cite
|
Sign up to set email alerts
|

All naturally occurring autoantibodies against the NMDA receptor subunit NR1 have pathogenic potential irrespective of epitope and immunoglobulin class

Abstract: Autoantibodies of the IgG class against N-methyl-D-aspartate-receptor subunit NR1 (NMDAR1) were first described in anti-NMDAR encephalitis and seen as disease indicators. Recent work on together over 5000 individuals challenged this exclusive view by showing age-dependently up to 420% NMDAR1-autoantibody seroprevalence with comparable immunoglobulin class and titer distribution across health and disease. The key question therefore is to understand the properties of these autoantibodies, also in healthy carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
124
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 41 publications
14
124
1
3
Order By: Relevance
“…To date, studies that found NR1‐IgM have not related their presence to ongoing de novo production from recent germinal center reactions 20, 21. However, in our study, NR1‐IgM rates were surprisingly high in NMDAR‐antibody encephalitis patients and low in disease controls 22. The higher detection rate in the target population may be explained by use of live cell‐based assays, which are known to enhance sensitivity of NR1‐IgG detection 23.…”
Section: Discussioncontrasting
confidence: 57%
“…To date, studies that found NR1‐IgM have not related their presence to ongoing de novo production from recent germinal center reactions 20, 21. However, in our study, NR1‐IgM rates were surprisingly high in NMDAR‐antibody encephalitis patients and low in disease controls 22. The higher detection rate in the target population may be explained by use of live cell‐based assays, which are known to enhance sensitivity of NR1‐IgG detection 23.…”
Section: Discussioncontrasting
confidence: 57%
“…HEK293T cells (50,000) cultured at 37°C/8% CO 2 in DMEM (high glucose, Life Technologies, Carlsbad, USA) were seeded on a 35 -mm dish, grown for 3 days, and transfected with 3 µg of myc-His-tagged GluN1-1b cloned into pcDNA4/TO/myc-His A (Invitrogen, Carlsbad, USA) using Metafectene-Pro (Biontex, Munich, Germany) [10]. One day post transfection, cells were split onto five poly-Dlysine-coated coverslips in a 35 -mm dish and 1 day later, they were fixed with 5% paraformaldehyde (PFA) for 20 min, washed 5× (PBS), permeabilized with 0.1% Triton X-100 for 5 min, again washed 5× (PBS), and blocked with 5% normal goat serum (NGS; Sigma-Aldrich, Munich, Germany) for 1 h. After five PBS washes, cells were incubated with serum and monoclonal mouse anti-myc IgG (clone 9E10, Hollmann-Lab, Bochum) for 1 h, washed with 10× (PBS), incubated for 1 h with fluorescein-labeled goat anti-monkey IgM (072-11-031; KPL, Gaithersburg, USA) and AlexaFluor®594-labeled goat anti-mouse IgG (A11005; Thermo Fisher) secondary AB, and PBS washed 5×.…”
Section: Nmdar1-ab Igm Screening In Monkey Samplesmentioning
confidence: 99%
“…To assess AB functionality, human IPSC-derived neurons were exposed to dialyzed serum [10]. For each species, arbitrarily selected seronegative (N = 1) and seropositive samples (N = 2-3) were analyzed.…”
Section: Endocytosis Assaymentioning
confidence: 99%
See 2 more Smart Citations